Happy singlehood : the rising acceptance and celebration of solo living - Kislev, Elyakim (Oakland, California : University of California Press, 2019)
"The singles' population is rapidly growing and doing so happily ever after. Instead of marrying, many singles nurture extensive social networks, develop self-sufficient lifestyles, and make flexible living arrangements. Happy Singlehood delves into these trends in a multi-method research and asks: "Which strategies help singles fight loneliness and social pressure? What can educators, policymakers, and urban planners do for happy singles? How will the future of happy singlehood look like?" Addressing these questions with authentic voices from around the world and up-to-date statistics, this book illuminates the coming age of singlehood. Singles and couples alike can benefit from seeing singlehood as a legitimate lifestyle, making the best out of whatever marital choice they take"--Provided by publisher.
Includes bibliographical references (pages 195-257) and index.
Keywords: Single people